(untitled) (Dhaka University Journal of Science, 2024)
Attempts have been made to synthesize vanadium doped rubidium hexagonal tungsten bronzes with the nominal composition RbxVyW1-yO3 (x = 0.30, 0.25, and 0.0 ≤ y ≤ x). The samples were synthesized using the solid state synthesis method in a silica glass tube under vacuum at (10-2 Torr) 700°C. The X-ray diffraction measurements reveal that a pure hexagonal tungsten bronze (HTB) phase can be formed with a 60% replacement of W5+ by V5+. The systematic incorporation of vanadium into the HTB lattice, as well as the reduction of V/W-O bond lengths in the xy plane and the lengthening of these bonds in the crystallographic c direction, are also revealed by Rietveld structure refinement of XRD data. The XRD results are supported by FTIR absorption spectra of the oxidized phases. Furthermore, an absorption signature develops as a function of y and exhibits a considerable increase in intensity with the eventual replacement of W5+ by V5+, showing a large decrease in the metallic like contribution and revealing the compounds’ nonmetallic nature. Elemental analysis indicates good agreement with nominal values, demonstrating that vanadium was systematically incorporated into the RbxVyW1-yO3 system. Dhaka Univ. J. Sci. 72(1): 77-84, 2024 (January)